2019
DOI: 10.3319/tao.2018.12.09.03
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Milun Fault: The coseismic surface rupture zone of the 2018/02/06 ML 6.2 Hualien earthquake, Taiwan

Abstract: On 6 February 2018, a M L 6.2 earthquake struck the east coast of Taiwan and caused more than 200 casualties in the Hualien area. The mainshock initiated at a shallow depth of 6.3 km and was accompanied by numbers of foreshocks and aftershocks. Coseismic ruptures widely occurred along the Milun Fault with various deformational structures and caused a variety of damage. Extensive field survey and drone-based images reveal the distribution of offsets and the characteristics of the surface ruptures. The major sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
(35 reference statements)
2
15
0
Order By: Relevance
“…5). Although In-SAR technique could not well detect along-track coseismic displacement (subparallel to the strike of the Milun fault), however if we decompose of the fault-parallel displacement revealed by the optical image correlation of aerial photos (the maximum offset of 1 m from ) and field survey (the maximum offset of ~ 77 cm from Huang et al 2019), the eastward motions are consistent with our results. The main westward coseismic motion dominates in the footwall of the Lingding fault, which is consistent with the observation from GPS stations showing a NW motion in this area.…”
Section: D-insar Resultssupporting
confidence: 87%
“…5). Although In-SAR technique could not well detect along-track coseismic displacement (subparallel to the strike of the Milun fault), however if we decompose of the fault-parallel displacement revealed by the optical image correlation of aerial photos (the maximum offset of 1 m from ) and field survey (the maximum offset of ~ 77 cm from Huang et al 2019), the eastward motions are consistent with our results. The main westward coseismic motion dominates in the footwall of the Lingding fault, which is consistent with the observation from GPS stations showing a NW motion in this area.…”
Section: D-insar Resultssupporting
confidence: 87%
“…They showed that surface ruptures follow the traces of the Milun fault and northern Linding fault. The mapped surface ruptures are typically appeared in en échelon arrays or distributed fractures rather than a through-going fault, which are comparable to the results of Hsu et al (2019) and Huang et al (2019). They considered that the appearances of the along-strike variations of the surface rupture for the 2018 Hualien earthquake are different from the surface rupture patterns documented for the 1951 Hualien-Taitung event.…”
mentioning
confidence: 61%
“…Three studies focused on field investigations of the surface coseismic ruptures using field geology, stress analyses and unmanned aerial systems photogrammetry. Huang et al (2019) investigated the coseismic rupture patterns of the 2018 Hualien earthquake using the analyses from field survey and drone-based image results. They found that major ruptures occurred as arrays of Riedel shears and formed right-stepping step-overs and restraining bends in the linking damage zones along the Milun fault, where the rupture traces repeat the surface breaks of the 1951 M 7.3 Hualien-Taitung earthquake sequence.…”
mentioning
confidence: 99%
“…As inferred from the distribution of the aftershock, which ranged from the offshore Milun Fault to the Great Hualien area on land, the seismogenic fault should be a strike-slip fault with a westward dip in a northeast-southwest direction. The shock induced the activities on the Milun Fault and the Lingding Fault and caused a large-scale of surface ruptures along the fault line (Hsu et al , 2019Huang et al 2019;Lin et al 2019) -mainly concentrated at the north of Hualien County (Fig. 2 The Milun Fault is a left-lateral fault with a reverse component striking in a direction of north-south and extending from the southwest of the Chihsingtan beach to Hualien City along the west edge of the Milun Terrace.…”
Section: Geological Backgroundmentioning
confidence: 99%